Puerarin: A Potential Therapeutic for SARS-CoV-2 and Hantavirus Co-Infection - Liang, Weizheng; Li, Xiushen; Wang, Hao; Nie, Kechao; Meng, Qingxue; He, Junli; Zheng, Chunfu (Frontiers in Immunology, 2022)
Patients with Hantavirus-caused epidemic hemorrhagic fever (EHF) are at risk of contracting SARS-CoV-2. However, there is currently no validated EHF/SARS-CoV-2 strategy. Several studies have recently shown Puerarin, a natural product, to have potent antiviral properties. The goal of this study was to determine the mechanism of puerarin in EHF/SARS-CoV-2 patients. Using network pharmacology and bioinformatics, investigate the possible pharmacological targets, bioactivities, and molecular mechanisms of puerarin in treating EHF/SARS-CoV-2 patients. The study investigated the pathogenesis of COVID-19 and EHF and the signaling pathway impacted by puerarin. 68 common genes linked to puerarin and EHF/SARS-CoV-2 were discovered during the investigation. Using a protein-protein interaction (PPI) network, we identified RELA, JUN, NF-B1, NF-B2, and FOS as potential therapeutic targets using a protein-protein interaction (PPI) network. The bioactivity and signaling pathways of puerarin have also been demonstrated in the treatment of EHF and COVID-19. According to this study, puerarin could reduce excessive immune responses and inflammation through the NF-B, TNF, and HIF-1 signaling pathways. This research discovered that puerarin could be used to treat EHF/SARS-CoV-2 patients, as well as looking into its potential therapeutic targets and mechanisms.